2022
DOI: 10.4014/jmb.2110.10021
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Enhancing Effects of Crude Polysaccharides from Korean Ginseng Berries on Spleens of Mice with Cyclophosphamide-Induced Immunosuppression

Abstract: Panax ginseng C. A. Meyer is well known as traditional herbal medicine, and ginseng berries are known to exhibit potential immune-enhancing functions. However, little is known about the in vivo immunomodulatory activity of Korean ginseng berries. In this study, crude Korean ginseng berries polysaccharides (GBP) were isolated and their immunomodulatory activities were investigated using cyclophosphamide (CY)-induced immunosuppressive BALB/c mice. In CY-treated mice, oral administration of GBP (50-500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…The above results indicated that Echinacea extract could effectively repair the damage of the bursa of Fasciola, promote lymphocyte proliferation and improve the immune organ index. It was reported in several studies that the immune-enhancing effects of the polysaccharide components of herbal medicine were mainly achieved by significantly increasing the levels of TNF-α, IFN-γ, and IL-2 in serum ( Fan et al, 2013 ; Zhou et al, 2018 ; Liu et al, 2022 ; Nam et al, 2022 ), and Echinacea extract also increased the levels of these three cytokines in the serum in this trial. It is worth considering that there is a link between changes in serum levels of immune-related cytokines and changes in the intestinal flora.…”
Section: Discussionsupporting
confidence: 61%
“…The above results indicated that Echinacea extract could effectively repair the damage of the bursa of Fasciola, promote lymphocyte proliferation and improve the immune organ index. It was reported in several studies that the immune-enhancing effects of the polysaccharide components of herbal medicine were mainly achieved by significantly increasing the levels of TNF-α, IFN-γ, and IL-2 in serum ( Fan et al, 2013 ; Zhou et al, 2018 ; Liu et al, 2022 ; Nam et al, 2022 ), and Echinacea extract also increased the levels of these three cytokines in the serum in this trial. It is worth considering that there is a link between changes in serum levels of immune-related cytokines and changes in the intestinal flora.…”
Section: Discussionsupporting
confidence: 61%
“…Notably, in this study, compared to those in the NG group, the spleen indices in the CTX group were significantly lower (Fig. 1 E), which contradicts the findings of Lv [ 40 ], but aligns with the findings of Zhang, Nam, et al [ 41 , 42 ]. These starkly contrasting findings suggest the occurrence of differential immune disruption caused by CTX in different animal species, while the timing of the establishment of the immunosuppression model using cyclophosphamide is one of the key factors in the variability.…”
Section: Discussionsupporting
confidence: 56%
“…The spleen is an important immune organ of the body, which plays a role in indicating the strength of immune function [ 57 ]. The spleen index of AD-like mice induced by DNCB is shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%